(untitled) (Baghdad Science Journal, 2019)
In this paper, we investigate the basic characteristics of "magnetron sputtering plasma" using the target V2O5. The "magnetron sputtering plasma" is produced using "radio frequency (RF)" power supply and Argon gas. The intensity of the light emission from atoms and radicals in the plasma measured by using "optical emission spectrophotometer", and the appeared peaks in all patterns match the standard lines from NIST database and employed are to estimate the plasma parameters, of computes electron temperature and the electrons density. The characteristics of V2O5 sputtering plasma at multiple discharge provisos are studied at the "radio frequency" (RF) power ranging from 75 - 150 Watt and gas pressure (0.03, 0.05 and 0.007) torr. One can observe that the intensity of the emission lines increases with increasing the sputtering power. We find that the electron temperature excess drastically from 0.95 eV to 1.11eV when the emptying gas pressure excess from 0.03 to 0.05 Torr. On other hand excess electron temperature from 0.9 to 1.01 eV with increasing sputtering power from 100 to 125 Watt, while the electron density decrease from 5.9×1014 to 4.5×1014 cm-3 with increasing sputtering power. and electron density decrease with increasing of pressure from 4.25×1014 to 2.80×1014 cm-3, But the electron density maximum values 5.9×1014 at pressure 0.03 Torr.